PENGARUH ESTETIKA TERHADAP SIKAP PADA MEREK YANG DIMEDIASI OLEH SUMBER KREDIBILITAS DAN PERSEPSI TERHADAP MEREK RIA MIRANDA DI KOTA BANDA ACEH - Putri Widya Qadri; Permana Honneyta Lubis (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
The study aims to measure the effect of aesthtic to brand attitude with credibility source and perception of brand as a mediating variable at Ria Miranda brand in  Banda Aceh city. The sample used in this study was people that used Ria Miranda brand involving 130 respondens. Instrument used for data collecting was questionnaire. Purposive sampling was used as sampling technique. Hierarchical Linear Modelling  (HLM) was used as analysis method to determine the effect of variables involved. Based on the analysis results, it is indicated that aesthetic influence brand attitude, credibility source and perception of brand as a mediate the relationship between aesthetic and brand attitude.